2015
DOI: 10.1002/jwmg.985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of harvest indices for monitoring cougar survival and abundance

Abstract: Harvest indices are used by state wildlife management agencies to monitor population trends and set harvest quotas for furbearer species. Although harvest indices may be readily collected from hunters, the reliability of harvest indices for monitoring demography and abundance of the harvested species is rarely examined, particularly amongst large carnivores. The overall objective of this study was to assess whether cougar (Puma concolor) harvest statistics collected by wildlife managers were correlated with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Cougars are classified as a hunted game mammal across much of their current range (Anderson et al ), and state and provincial managers should clearly define population and harvest objectives for cougars that do not threaten their long‐term conservation. Anderson and Lindzey () and Wolfe et al () found that monitoring hunter success rates and ages of female cougars harvested provided guidance on appropriate harvest rates to reduce or maintain cougar densities. Management actions to reduce cougar densities may be short‐lived given the dispersal patterns and reproductive potential of cougars (Clark ).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Cougars are classified as a hunted game mammal across much of their current range (Anderson et al ), and state and provincial managers should clearly define population and harvest objectives for cougars that do not threaten their long‐term conservation. Anderson and Lindzey () and Wolfe et al () found that monitoring hunter success rates and ages of female cougars harvested provided guidance on appropriate harvest rates to reduce or maintain cougar densities. Management actions to reduce cougar densities may be short‐lived given the dispersal patterns and reproductive potential of cougars (Clark ).…”
Section: Management Implicationsmentioning
confidence: 99%
“…In particular, studies need to be carefully designed when trying to assess how the harvest of predators is related to variation in the vital rates of prey [80]. The connection between predator harvest, predator population dynamics and predation risk to ungulates is unclear and has rarely been evaluated [81]. This lack of clarity is worsened where predator harvest regulations are set in response to a combination of social, biological, and political factors or where harvest can fluctuate in response to any factors unrelated to population vital rates.…”
Section: Discussionmentioning
confidence: 99%
“…Under the food limitation and competition regulation hypotheses, hunting mortality ranging from 10–44% of independent pumas is expected to be additive, and reduce puma populations within a few months or years (Logan and Sweanor ; Anderson and Lindzey ; Robinson et al ; Wolfe et al , ). When this happens, hunting mortality limits puma populations, overriding natural limitation and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the sexual selection process is altered (Murphy ; Logan and Sweanor , ; Mysterud ). Conversely, hunting mortality averaging 5–18% of independent pumas (Anderson and Lindzey , Wolfe et al ) or its elimination, could result in higher puma survival and population growth, if not already limited by food, maintain an older age structure, and allow for natural sexual selection processes (Logan and Sweanor , ). Recruitment of male pumas into local populations will depend primarily upon immigration, and of females, a combination of in situ reproduction and immigration (Seidensticker et al , Anderson et al , Logan and Sweanor ).…”
Section: Discussionmentioning
confidence: 99%